Impact of gestational diabetes mellitus in human placental mass - Reginatto, Cleiton Jonei; Subtil, Vinicius Mazzetti; Rodrigues, Lisandra Vieira; Valenti, Vitor Engrácia; Abreu, Luiz Carlos de; Gomes, Rayana Loch; Petenusso, Marcio (ABCS Health Sciences, 2016)
Introduction: Gestational diabetes mellitus (GDM) is a pathological alteration of maternal energy metabolism unleashed by the pregnant woman’s inability to produce sufficient amounts of insulin to compensate for glucose intolerance triggered by the action of placental lactogenic hormone (HPL). Given that plasma levels of HPL are proportional to the placenta mass and that they are close to the maximum period in which the placenta acquires its larger size and that hyperglycemia is manifested in pregnant women with GDM, it is possible to infer that there might be correlation between the placental mass and this disease. Objective: To evaluate whether there is correlation between GDM and placental mass. Methods: Descriptive, cross-sectional and quantitative approach survey, which was conducted in a public hospital in Santa Catarina, Brazil. The survey included 20 pregnant women, 10 with and 10 without GDM, who agreed to participate in the study. Results: The average of placenta masses of the Control Group was 505.63±12.18 g, while of the GDM group it was 561,00 ±14.25 g. Conclusion: This study suggests that placental mass of pregnant women with GDM is significantly greater than the mass placenta of healthy pregnant women.